2017
DOI: 10.1161/jaha.117.006541
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Leukocyte Telomere Length and the Risk of Incident Atrial Fibrillation: The Framingham Heart Study

Abstract: BackgroundAdvancing age is a prominent risk factor for atrial fibrillation (AF). Shorter telomere length is a biomarker of biological aging, but the link between shorter telomere length and increased risk of AF remains unclear. We examined the association between shorter leukocyte telomere length (LTL) and incident AF.Methods and ResultsWe included AF‐free participants from the observational Framingham Heart Study Offspring cohort from 1995 to 1998, who had LTL measurements. We examined the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
15
1
1
Order By: Relevance
“…In the present study, we found a significant positive association between telomere length and systolic blood pressure in LBW subjects, which was however, not significant in the pooled data set. This is supported by a study in adult females were no association between telomere length and blood pressure was found 36 and further by a study were no association between telomere length and the risk of incident atrial fibrillation was observed 37 . Thus, more studies are needed to clarify the relationship between telomere length and cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, we found a significant positive association between telomere length and systolic blood pressure in LBW subjects, which was however, not significant in the pooled data set. This is supported by a study in adult females were no association between telomere length and blood pressure was found 36 and further by a study were no association between telomere length and the risk of incident atrial fibrillation was observed 37 . Thus, more studies are needed to clarify the relationship between telomere length and cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 79%
“…A flow diagram of the study identification and selection process is shown in Figure . A total of 22 entries were retrieved from the databases, of which 5 studies met our inclusion criteria . After including the data from this study, a total of 6 studies were included in the final meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 entries were retrieved from the databases, of which 5 studies met our inclusion criteria. 1,2,6,14,15 After including the data from this study, a total of 6 studies were included in the final meta-analysis. The details of the NOS quality assessment are shown in Table S1.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…Roberts et al, [ 15 ] Siland et al, [ 16 ] and Staerk et al [ 17 ] conducted longitudinal study designs rather than cross-sectional study focusing on the relationship between incidence of AF and LTLs. These 3 prospective studies came to similar conclusions, finding that aging and short LTL were independent risk factor for AF.…”
Section: Discussionmentioning
confidence: 99%